Objective assessment of eye alignment and disparity-driven vergence in Parkinson’s disease - Gupta, Palak; Murray, Jordan M.; Beylergil, Sinem Balta; Jacobs, Jonathan; Kilbane, Camilla W.; Shaikh, Aasef G.; Ghasia, Fatema F. (Frontiers in Aging Neuroscience, 2023)
Background: Self- reported diplopia is described in up to one-third of Parkinson’s disease (PD) patients. Objective: The purpose of our study was to expand our understanding of the mechanistic underpinnings of diplopia in PD. We hypothesize that the time-based control of eye alignment and increased eye deviation under binocular viewing will be related to the fusion-initiating and fusion-maintaining component deficits of disparity-driven vergence in PD. Methods: We used high-resolution video-oculography to measure eye alignment under binocular and monocular viewing and disparity-driven vergence in 33 PD and 10 age-matched healthy participants. We computed eye deviation and time-based control of eye alignment, occurrence of conjugate saccadic eye movements, latency and gain of vergence (fusion-initiation) and variance of eye position at the end of dynamic vergence (fusion-maintenance). Results: We categorized PD subjects into three groups, considering their time-based control of eye alignment as compared to healthy controls in binocular viewing. Group1=45% had good control and spent >80% of the time when the eyes were well-aligned, Group2=26% had intermediate control and spent <80% but greater >5% time when the eyes were well-aligned and Group3=29% had very poor control with increased eye deviation majority of the times (<5% time when the eyes were well-aligned. All three groups exhibited greater eye deviation under monocular viewing than controls. PD subjects exhibited fusion-initiating and fusion-maintaining vergence deficits (prolonged latencies, reduced vergence gain, increased variance of fusion-maintaining component) with greater probability of saccadic movements than controls. Group2 and Group3 subjects were more likely to exhibit failure to initiate vergence (>20%) than Group1(13%) and controls (0%) trials. No significant difference was found in the Unified Parkinson's Disease Rating Scale (UPDRS – a tool to measure severity of PD) values between the three PD groups (Group1=33.69±14.22, Group2=38.43±22.61, Group3=23.44±1, p>0.05). Conclusions: Majority of PD subjects within our cohort had binocular dysfunction with increased eye deviation under monocular viewing and disparity-driven vergence deficits. PD subjects with intermediate or poor control of eye deviation under binocular viewing had greater fusion-initiating and fusion-maintaining vergence deficits. The study highlights the importance of assessing binocular dysfunction in PD subjects independent of the severity of motor symptoms.